Do E-Wallets Altered Consumptive Behavior? Qualitative Study Of Gen Z In Jambi City - Hamzah, Muhammad Maulana; Rafidah; Laode, Jafar Shadiq (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2023)
This research was conducted to find out and analyze the factors that influence the use of e-wallets and how the behavior of generation Z in the city of Jambi forms. This study uses a qualitative approach. The data sources used are primary and secondary data sources. While the data collection technique used in this study is using observation interviews and documentation. The results showed that the factors that influence the use of e-wallets in generation Z in the city of Jambi are divided into the main factors namely, Benefit, Convenience and supporting factors including, Cost Factor, Popular Factor, Efficiency Factor, Speed Factor, Factor Security, Convenience Factors, Promo and Discount Factors, and Pulse/Token Payment Service Business Factors. Thus there are two main factors and eight supporting factors. Transaction purposes that indicate that using e-wallets encourage people to be more consumptive are top-up Games and Online Shopping. Based on observation from 112 informants, out of 112 informants, 62% of them feel more consumptive when using e-wallets. Meanwhile, 38% felt that they were not consumptive and 4% were mediocre.